1995
DOI: 10.1128/jb.177.16.4638-4644.1995
|View full text |Cite
|
Sign up to set email alerts
|

An early A-signal-dependent gene in Myxococcus xanthus has a sigma 54-like promoter

Abstract: A-signaling plays an essential role in the early stages of Myxococcus xanthus fruiting body development. Expression of the 4521 gene, which is regulated at the level of RNA accumulation, depends on starvation and on A-signaling. To identify the cis-acting regulatory elements which allow gene 4521 to respond to the nutritional and A-factor signals, the 4521 transcription start site was mapped. The region just upstream of the start site showed sequence similarity to the 54 family of promoters and to the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 43 publications
0
66
0
Order By: Relevance
“…This defect exemplifies a requirement for proper spacing between the Ϫ12 and Ϫ24 elements, as has been observed elsewhere (3,29,(43)(44)(45). Strict spacing between promoter elements helps to distinguish sigma-54 promoters from sigma-70 promoters (2,18).…”
Section: Dynamics Of Act Operon Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…This defect exemplifies a requirement for proper spacing between the Ϫ12 and Ϫ24 elements, as has been observed elsewhere (3,29,(43)(44)(45). Strict spacing between promoter elements helps to distinguish sigma-54 promoters from sigma-70 promoters (2,18).…”
Section: Dynamics Of Act Operon Expressionmentioning
confidence: 99%
“…This resembles the extensively studied M. xanthus sigma-54 pilA promoter (71). It also resembles the M. xanthus ⍀4521 promoter, for which sequence mutations have indicated sigma-54 specificity (29). The sigma-54 gene (rpoN), which is in single copy, is essential for M. xanthus development.…”
Section: Dynamics Of Act Operon Expressionmentioning
confidence: 99%
“…Both s 70 - (Table 4a) and s 54 - (Table 4b) dependent promoter sequences were identified, each with homology to their respective consensus sequences (Hawley and McClure, 1983;Barrios et al, 1999) and those reported earlier in E. coli (Dombroski et al, 1996), Myxococcus xanthus (Keseler and Kaiser, 1995) and Pseudomonas aeruginosa (Medina et al, 2003). In addition, a putative in-frame translation initiation codon and corresponding potential ribosome-binding site were identified for each transcript arising from a potential TSP (Table 4).…”
Section: Tsp Potential Promotersmentioning
confidence: 99%
“…We selected for spontaneous rifampicin-resistant mutants and kanamycin-resistant transformants carrying the plasmid pREG1727 [44]. Only marked clones that exhibited no significant marker effects on focal traits relative to their unmarked parent were used for further experiments (data available upon request).…”
Section: Materials and Methods (A) Clonesmentioning
confidence: 99%